Recovery from addiction : a practical guide to treatment, self-help, and quitting on your own - Cloud, William, 1947-; Granfield, Robert, 1955- (New York University Press, 2001)
Millions of people enter or seriously consider entering alcohol or drug treatment each year. In their understandable state of urgency, most first-time treatment seekers and their loved ones may rush to the first treatment option they encounter. They are unlikely to be aware of why one form of intervention would be a good choice for their particular problem or why some approaches may, under some conditions, actually be harmful. Lacking reliable information, they are unable to make informed choices. Recovery from Addiction offers a concise, reader-friendly guide for substance dependent persons,